Gallbladder and the risk of polyps and carcinoma in metachromatic leukodystrophy. (5th July 2016) - van Rappard, Diane F.; Bugiani, Marianna; Boelens, Jaap J.; van der Steeg, Alida F.W.; Daams, Freek; de Meij, Tim G.J.; van Doorn, Martine M.A.C.; van Hasselt, Peter M.; Gouma, Dirk J.; Verbeke, Jonathan I.M.L.; Hollak, Carla E.M.; van Hecke, Wim; et al.
Abstract : Objectives: To assess frequency of gallbladder polyposis and carcinoma in metachromatic leukodystrophy (MLD). Methods: We evaluated 34 patients with MLD (average age 16.7 years, age range 2–39 years) screened for gallbladder abnormalities by ultrasound. In the case of cholecystectomy, findings at pathology were reviewed. Results: Only 8 of 34 patients (23%) had a normal gallbladder at ultrasound. Gallbladder polyps were visible in 8 patients (23%). Cholecystectomy was performed in 11 patients (32%). In these, pathology revealed various abnormalities, including hyperplastic polyps, intestinal metaplasia, prominent Rokitansky-Aschoff sinuses, and sulfatide storage. Conclusions: Our results demonstrate that gallbladder involvement is the rule rather than the exception in MLD. The high prevalence of hyperplastic polyps, a known precancerous condition, and one death from gallbladder carcinoma at a young age suggest that MLD predisposes to neoplastic gallbladder abnormalities. As novel therapies for this patient group are emerging leading to increased life expectancy, we recommend screening for gallbladder abnormalities by ultrasound in order to prevent early death.